The role of bank relationships when firms are financially distressed - Höwer, Daniel (Journal of Banking & Finance, 2016)
Banks are better suited than other financing partners to process information in order to make efficient liquidations. But their ability depends on bank characteristics and incentives. In addition, the strength of the main bank relationship influences the bank’s ability to make efficient liquidations. I study the effect of bank characteristics and bank relationships in situations where firms are financially distressed. Do the chances of a financially distressed firm to improve or to close depend on the bank? Does the survival of a financially distressed firm depend on its main bank relationship? Using German data from 2000–2013, I analyze the effect of a bank’s organizational complexity, non-performing customers, and the strength of main bank relationships at the bank and firm level. I find that high shares of non-performing clients provide negative incentives. Banks can make more efficient liquidations if they are regionally active and have close relationships with the firm.